Case report: Rapidly progressive desmoid tumor after surgery for esophagogastric junction cancer and slowly progressive primary desmoid tumor: a report of two cases and literature review - Li, Chuan-Ying; Gao, Yan-Peng; Jia, Ming-Hao; Zhou, Yuan; Xu, Jia-You (Frontiers in Oncology, 2024)
Desmoid tumor (DT) is a rare locally aggressive but non-metastatic mesenchymal soft tissue neoplasm that predominantly occurs in the abdominal wall, abdominal cavity, and extremities. Its occurrence in the mesentery is relatively uncommon.This article reports two cases of desmoid tumor treated at the Department of Gastrointestinal Surgery, Weifang People's Hospital. The first case was a 59-year-old male patient who had previously undergone surgery for esophagogastric junction cancer. Postoperatively, he developed an intraabdominal mass that rapidly increased in size within three months. The second case was a 60-year-old male patient who incidentally discovered a mass in the left lower abdomen. Both patients underwent surgical treatment, and the postoperative pathological diagnosis was mesenteric desmoid tumor.The treatment of desmoid tumor remains challenging. Simple surgical resection often yields unsatisfactory outcomes, and the efficacy of adjuvant radiotherapy and chemotherapy is also limited.Further research and clinical practice are necessary to improve diagnostic and therapeutic strategies, aiming to enhance patient survival and quality of life.